Exploring Reflective Teaching through Informed Journal Keeping and Blog Group Discussion in the Teaching Practicum - Edgar Alirio Insuasty; Liliana Cecilia Zambrano Castillo (Universidad Nacional de Colombia, 2010)
This article reports the findings of a study which examined how student teachers could be empowered as more reflective practitioners through journal keeping and blog group discussions. It was carried out with six student teachers who developed their practicum over six months. Data were collected through journals, blogs, metaphors, conferences and a questionnaire. The results demonstrated that student teachers enriched their perceptions about what reflective teaching implied. Furthermore, journal keeping was approached as an informed process by virtue of which student-teachers could go beyond the descriptive documentation of what happened in their classes. Their journal entries also revealed reflective references, most of which were mainly focused on evaluating teaching, diagnosing and solving problems.